2020
DOI: 10.1111/pace.14130
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion tool software for pulmonary vein occlusion verification in atrial fibrillation cryoballoon ablation

Abstract: Background Optimal pulmonary vein (PV) occlusion, usually verified with selective contrast injection, is mandatory to obtain an effective PV isolation during cryoballoon (CB) ablation. Aim of the study The purpose of this study was to verify the feasibility and the accuracy of a new dielectric sensing system in assessing PV occlusion during CB ablation in patients with atrial fibrillation (AF). Methods We enrolled 28 consecutive patients with paroxysmal or persistent AF. After transseptal access, a detailed im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
5
18
0
Order By: Relevance
“…Interestingly, the specificity of the occlusion tool analyzed for each PV shows a lower value for LIPV (60%) as compared to the remaining PVs (LSPV 100%, RIPV 90%, RSPV 100%). Cauti et al has previously shown that there is a predicted variation in specificity for each PV (27). Our results confirm the hypothesis that a variation might exist for the accuracy of the occlusion tool in the present version when approaching some veins such as the LIPV.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, the specificity of the occlusion tool analyzed for each PV shows a lower value for LIPV (60%) as compared to the remaining PVs (LSPV 100%, RIPV 90%, RSPV 100%). Cauti et al has previously shown that there is a predicted variation in specificity for each PV (27). Our results confirm the hypothesis that a variation might exist for the accuracy of the occlusion tool in the present version when approaching some veins such as the LIPV.…”
Section: Discussionsupporting
confidence: 88%
“…The first step of our strategy consisted of a straightforward CBA based PVI which was guided by using the occlusion tool software module provided by the new imaging system in addition to conventional PV angiography. We were able to confirm the results of Cauti et al (27) and Rillig et al (17). The sensitivity and specificity of the occlusion tool were high.…”
Section: Discussionsupporting
confidence: 85%
“…Those features can improve the procedural efficiency. The previous studies showed the feasibility of using the KODEX-EPD system in radiofrequency or cryoballoon ablation in clinical practice (14,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…In the event of a partial occlusion, the effects of balloon maneuvering to obtain better and complete occlusion are shown in real time without the need for several checks and the use of multiple dye injections and angiograms. Cauti et al 12 tested the accuracy of the software module in 105 PVs during cryoballoon ablation by verifying with contrast medium injection and reported good sensitivity of 91% and specificity of 76%. Cryoballoon visualization: Direct visualization of the cryoballoon catheter itself would allow maneuvering for complete occlusion while further reducing fluoroscopy time, contrast injections, and, potentially, PV stenosis.…”
mentioning
confidence: 99%